Центральна могила Великого Рижанівського кургану - Скорий, С.А.; Хохоровські, Я.; Григор’єв, В.П.; Ридзевські, Я. (Археологія, 1999)
Публікується інформація про відкриття непограбованої центральної могили у поховальній пам'ятці скіфської знаті — Великому Рижанівському кургані. Исследованное Украинско-Польской экспедицией в 1996 г. погребение скифской знати избежало ограбления. Могила представляла собой катакомбу площадью более 30 м2. Во входной яме находились сопровождающие захоронения — охранника и коня с деталями упряжи.
Погребальная камера имитировала жилое помещение, разделенное в центре материковой фигурной перегородкой, напоминающей печь. Пол был выстлан циновками из камыша и луба, стены и потолок драпированы тканью.
Погребенный (мужчина знатного происхождения 45—50 лет) лежал на деревянном помосте в сопровождении многочисленных вещей, в том числе из драгоценных металлов, и обилия жертвенной пищи. Особый интерес представляют золотые украшения женского парадного головного убора и серебряный кубок, украшенный сценами, выполненными в скифском зверином стиле.
Погребение предварительно датируется 1-ой четвертью III в. до н. э. Есть основания считать, что знатный покойник являлся главой (номархом?) одной из южных лесостепных областей (междуречье Гнилого и Горного Тикича), вошедших в состав Великой Скифии в IV в. до н. э. The paper focuses on the burials of Scythian nobles investigated by a joint Ukrainian and Polish expedition in 1996; the grave was not robbed. The grave was a kind of catacomb that occupied a floor space of 30 square meters. There were additional burials of a guardian and a horse with the details of harness in the entrance pit of the grave.
The burial room was made in the form of an apartment divided into two parts by a figured partition made of subsoil; the partition resembles a furnace. The floor was covered with mats made of reed and bast; the walls and the ceiling were draped with cloth.
The deceased nobleman (45-50 years old) was lowered on the wooden podium and accompanied by a lot of belongings including those made of precious metals and by a parting food. It is worth mentioning golden decorations for a female formal headdress and a silver goblet ornamented with the scenes in the Scythian Animal Style.
The burials are preliminary attributed to the first quarter of the third century BC. There are strong grounds for believing that the deceased nobleman was a head (Nomarh?) of one of the Southern Forest-Steppe Region (between Hnyly Tikych River and Hirsky Tikych River) included in the Great Scythia in the fourth century BC.